2008
DOI: 10.1086/590117
|View full text |Cite
|
Sign up to set email alerts
|

Dengue in Vietnamese Infants—Results of Infection‐Enhancement Assays Correlate with Age‐Related Disease Epidemiology, and Cellular Immune Responses Correlate with Disease Severity

Abstract: The pathogenesis of severe dengue is not well understood. Maternally derived subneutralizing levels of dengue virus-reactive IgG are postulated to be a critical risk factor for severe dengue during infancy. In this study, we found that, in healthy Vietnamese infants, there was a strong temporal association between the Fc-dependent, dengue virus infection-enhancing activity of neat plasma and the age-related epidemiology of severe dengue. We then postulated that disease severity in infants with primary infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 24 publications
12
137
0
11
Order By: Relevance
“…[48][49][50] These virion-binding, non-neutralising antibodies are thought to enhance the risk of clinically apparent and severe dengue through a process of ADE. [51][52][53][54] In support of this hypothesis, neat plasma from 6-month old healthy Vietnamese infants enhances the infectivity of DENV-2 in Fc receptor bearing cells significantly more than plasma collected at the time of birth or at 1-yr of age. 52 Concerns about ADE have led to fears that a vaccine could contribute to increased disease severity due to re-infection in the presence of incomplete protection to one or more serotypes.…”
Section: The Humoral Immune Response and Antibody-dependent Enhancementmentioning
confidence: 95%
See 2 more Smart Citations
“…[48][49][50] These virion-binding, non-neutralising antibodies are thought to enhance the risk of clinically apparent and severe dengue through a process of ADE. [51][52][53][54] In support of this hypothesis, neat plasma from 6-month old healthy Vietnamese infants enhances the infectivity of DENV-2 in Fc receptor bearing cells significantly more than plasma collected at the time of birth or at 1-yr of age. 52 Concerns about ADE have led to fears that a vaccine could contribute to increased disease severity due to re-infection in the presence of incomplete protection to one or more serotypes.…”
Section: The Humoral Immune Response and Antibody-dependent Enhancementmentioning
confidence: 95%
“…[51][52][53][54] In support of this hypothesis, neat plasma from 6-month old healthy Vietnamese infants enhances the infectivity of DENV-2 in Fc receptor bearing cells significantly more than plasma collected at the time of birth or at 1-yr of age. 52 Concerns about ADE have led to fears that a vaccine could contribute to increased disease severity due to re-infection in the presence of incomplete protection to one or more serotypes. This hypothetical concern needs to addressed by careful, long-term follow-up of vaccine recipients.…”
Section: The Humoral Immune Response and Antibody-dependent Enhancementmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been suggested that CD8 ϩ and CD4 ϩ T-lymphocyte activation is associated with severity of dengue infection. 58 We observed a small decrease in the percentage of CD4 ϩ T cells but no changes in the percentage of CD8 ϩ T cells and in the spleen of DENV infected WT and J␣18 Ϫ/Ϫ mice ( Figure 5C). However, although both CD4 ϩ and CD8 ϩ T cells expressed more CD69 in DENV-infected WT mice, this enhancement was less important in infected J␣18 Ϫ/Ϫ mice.…”
Section: J␣18 ϫ/ϫ Mice Exhibit Decreased Activation Of Nk Cells and Nmentioning
confidence: 80%
“…[57][58][59] Thus, we measured the effect of endogenous iNKT cell activation on the frequency and activation of these other cells. DENV infection was associated with reduced frequency of NK cells ( Figure 5A) and enhanced percentage of neutrophils ( Figure 5B) in the spleen of WT mice.…”
Section: J␣18 ϫ/ϫ Mice Exhibit Decreased Activation Of Nk Cells and Nmentioning
confidence: 99%